«Համատարած աշխարհացոյցի»-ի գունազարդ տպագրության հետքերով - Զարգարյան, Տիգրան Կարոյի (Հայկական գրադարանային ասոցիացիա)
In 1695 in Amsterdam, the Armenian printing house headed by Tovmas Vanandetsi pub-lished a unique work; the first printed map of the world in Armenian “Hamatarats Ashkharhat-suyts” (Geographic Map of the World). The first large-scale map of both hemispheres in Armenian was considered the best and one of the most reliable maps at the time. The world map was designed in the style of Western cartography. Later this map was reproduced in Venice in colours, thanks to the efforts of the Mekhitarist Congregation fathers. In this article based on the archival documents the history of creating that coloured map is provided. A question is posed: is this an old-print map, and how should the bibliographic description of this map look?
Keywords: Հայ հնատիպ գիրք; Մատենագիտություն; Հայ տպագրության պատմություն; Մխիթարյան միաբանություն